2016
DOI: 10.3122/jabfm.2016.03.150256
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Continuity Improves Diabetic Health Outcomes: From Free Clinics to Federally Qualified Health Centers

Abstract: Introduction: There are a number of well-established barriers to accessing primary care. The LINKED Study set out to improve primary care usage through 1-on-1 counseling and referrals for patients with diabetes being treated at local free clinics. We hypothesized that this educational intervention paired with expedited referral would increase the use of federally qualified health centers (FQHCs) as a source of health care and ultimately lead to improved diabetic health.Methods: Medical student volunteers couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…This enables hyperlipaemia control to be determined by multiple measures which increases the reliability of the results. Although, medical student appointments were associated with statistically significant increases in BMI amongst patients with diabetes, body weight was not reported to support whether this negative result is clinically meaningful or not [39,44]. Two retrospective studies did not report how weight was measured (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This enables hyperlipaemia control to be determined by multiple measures which increases the reliability of the results. Although, medical student appointments were associated with statistically significant increases in BMI amongst patients with diabetes, body weight was not reported to support whether this negative result is clinically meaningful or not [39,44]. Two retrospective studies did not report how weight was measured (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this lack of reporting on what the students did sometimes impacted on how the patient outcomes could be interpreted. For example, whether medical students counselled patients, dispensed medication or provided both services were not reported [39,44]. Without this detail, it was difficult to determine if the medical intervention could have resulted in weight loss and reduction in BMI as the reported patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This special issue also features 4 unique SDOH interventions that span different places, people, and processes. Mehta et al 14 directly tackled a lack of health insurance and the cost of medical care when delivering in free clinics 1-on-1 counseling for high-risk patients with diabetes and referring them to local federally qualified health centers. They found that this warm hand-off led to improved glycemic control and more stable health care access for these patients at federally qualified health centers.…”
Section: Using Social Determinants Data To Inform Interventionsmentioning
confidence: 99%